Coaches' Adoption and Implementation of Sport Canada's Long-Term Athlete Development Model. (10th July 2015) - Beaudoin, Charlotte; Callary, Bettina; Trudeau, François
This work explores the adoption and implementation of Sport Canada's long-term athlete development (LTAD) model by coaches and tries to understand the barriers to and enablers of these processes. LTAD adoption was studied in 14 coaches (5 female, 9 male) in seven sports while implementation was assessed among 10 different coaches (2 female, 8 male) from nine sports. Semistructured interviews ascertained coaches' perceptions of and experiences with the LTAD model in their coaching practice. Coaches adhered to the global vision and general principles of LTAD. However, several barriers to LTAD adoption and implementation were identified. A mismatch between the model's long-term and the short-term visions of results in sport was perceived as deterrent to LTAD adoption and implementation. Coaches involved in early development sports mentioned a lack of compatibility of LTAD with the demands of their sport. Coaches also perceived complexity in LTAD athlete's developmental stage determination and the identification of "windows of opportunity" or critical periods. These barriers should be addressed to complete diffusion of LTAD among Canadian coaches.